Barcode-Karten as Learning Development to Improve Vocabulary Knowledge about German Language - Desti Nur Aini; Maura Safira Demara (West Science Interdisciplinary Studies, 2023)
The quality education process in learning foreign languages, mainly German, must be supported by learning media. To improve vocabulary knowledge about German Artikel with the Haustiere theme needs to be supported by "Barcode-Karten" as the purpose of this research. Multimedia-based learning media utilizes audio, text, and images by combining barcodes, links, and tools with that students are interested in finding out, interacting, and communicating. Borg and Gall's research and development model was modificated in this study. The validation and trial phases have been carried out on the development of Barcode-Karten media. Quantitative data in the form of assessment scores with a Likert scale and qualitative data were obtained from criticism and suggestions through questionnaires to validators and students of class XI Cross-Interest German Language at SMA Laboratorium UM. Data were analyzed using qualitative descriptive analysis techniques. The function of this media can bring out the desire and motivation and positively influence on students' vocabulary mastery. In addition, Barcode-Karten is worthy of being a learning medium to improve the knowledge of German vocabulary with the Haustiere theme.